OLED thin film fabrication from poorly soluble terbium o-phenoxybenzoate through soluble mixed-ligand complexes - Kalyakina, Alena S.; Utochnikova, Valentina V.; Sokolova, Elena Yu; Vashchenko, Andrey A.; Lepnev, Leonid S.; Van Deun, Rik; Trigub, Alexander L.; Zubavichus, Yan V.; Hoffmann, Michael; Mühl, Susan; Kuzmina, Natalia P. (Organic electronics, 2016)
Features and advantages of the approach of the luminescent thin film deposition of non-volatile and non-soluble lanthanide aromatic carboxylates were exemplified by thin film deposition of terbium o-phenoxybenzoate Tb(pobz)3(H2O)2 (I) with quantum yield measured to be 96%. This approach is based on the formation and decomposition of mixed-ligand complexes, and thus mixed-ligand complex Tb(pobz)3(MG)(H2O)2 (II) (MG – monoglyme) was synthesized, characterized and used as a precursor for I thin films. Electroluminescent (EL) properties of high quality thin films of I and those with suitable host material were studied in a series of OLED devices. [Display omitted] •Mixed-ligand complex Tb(pobz)3(monoglyme)(H2O)2 was used as precursor for thin films of Tb(pobz)3 with quantum yield of 96%.•Deposited thin films with roughness down to 2.3 nm and transparency up to 95% were successfully tested in OLED devices.•Mixed layer composition was thoroughly examined with an emphasis on luminescence and EXAFS spectroscopy.